The Impact Of The Continuation Of The New Normal In Teaching And Learning In Indonesia Recommendations And Implementation - Wismanto Hadi, Wahyu; Susilowati Dedeh, Lilik; Rodiah; Vepti Mutmainah; Arsita Pratiwi (CV. Inara, 2022)
Given the COVID-19 and normality of new, colleges and universities around the world must take action to secure the conditions of students and their staff, as well as members of the community.The pandemic of Coronavirus Disease (COVID-19) give a serious impact on access to higher education around the world. UNESCO Data mentioned in the year 2020 there were 1.1 billion students in the world (ranging from kindergarden to college) that apply the method of learning from home. In addition, there are about 63 million lecturers and teachers around the world who can't go teach. there are as many as 144 countries that apply the closure of the area or lockdown.One of the programs that must be quick in adaptation is to prepare human resources who are capable of adaptive in the era of the new normal. Specifically for college how in printing graduates involves the process of teaching and learning that focuses on the use of advanced technology, but at the same time human-centered that prioritizes the educational process by way of an interactive, two-way communication, collaborative and based on the spirit of long life learning.In the new normal era it is very important for educational institutions to develop innovative learning media will attract learners in following learning and will have an impact on learning outcomes both cognitively, affectively and psychomotorly. The attitude and behavior of friendly teachers, skills, and ownership of creative ideas owned by teachers can increase the motivation of learners.